Fatal Blastoid Variant Mantle Cell Lymphoma in a Patient with Sjögren's Syndrome - Fabio Bonilla-Abadía; Manuel A. Pérez; Evelyn Muñoz-Buitrón; Joaquín D. Rosales; Carlos A. Cañas; Gabriel J. Tobón (Case Reports in Rheumatology)
Primary Sjögren's syndrome (pSS) is an autoimmune disorder of the exocrine glands presenting with progressive ocular and oral dryness, parotid gland enlargement, and often with extraglandular manifestations. In this group of patients the risk of development of non-Hodgkin's lymphoma is 16-fold compared to healthy population, mainly of the MALT lymphoma type. This case reports a 52-year-old woman with pSS developing a progressively growing mass at face and neck compatible with blastoid variant mantle cell lymphoma and a fatal outcome.